Pengaruh Ukuran KAP, Audit Report Lag, Ukuran Perusahaan, dan Pergantian Manajemen Terhadap Auditor Switching - Fitri Dwi Jayanti; Bayu Kurniawan; Utami Puji Lestari (Universitas Ngudi Waluyo, 2020)
This tudy aims to examine and analyze the effect of KAP size, Audit Report Lag, Company Size, and Management Change against Switching Auditors in LQ45 companies listed on the Indonesia Stock Exchange (IDX) the period 2015-2018. The purposive sampling technique was used to obtain a sample size of 28 companies or 84 data in three years. The data analysis technique used is logistic regression with SPSS version 21. The results of this study showed that KAP size variables affect Auditor Switching, whereas Audit Report Lag, Company Size, and Management Change variables do not affect Auditor Switching